What Is Real and What Is Not in the Global FDI Network? - Damgaard, Jannick; Elkjaer, Thomas; Johannesen, Niels (Washington, D.C. : International Monetary Fund, 2019)
Macro statistics on foreign direct investment (FDI) are blurred by offshore centers with enormous inward and outward investment positions. This paper uses several new data sources, both macro and micro, to estimate the global FDI network while disentangling real investment and phantom investment and allocating real investment to ultimate investor economies. We find that phantom investment into corporate shells with no substance and no real links to the local economy may account for almost 40 percent of global FDI. Ignoring phantom investment and allocating real investment to ultimate investors increases the explanatory power of standard gravity variables by around 25 percent.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet